Knowledge level and access barriers related to sexual and reproductive health information among youth with disabilities in China: a cross-sectional study - Wenjuan Qi; Hongyan Li; Qiguo Lian; Xiayun Zuo; Chunyan Yu; Chaohua Lou; Xiaowen Tu (BMC, 2023)
Abstract Background Youth with disabilities have the same right to sexual and reproductive health (SRH) as their peers without disabilities. However, their needs and rights are often ignored. Little is known about the knowledge, needs and access barriers related to SRH information among youth with different types of disabilities in China. Methods A cross-sectional survey was carried out among 473 unmarried youth aged 15-24 with visual, hearing, physical disabilities in both urban and rural areas in China. Results Out of a maximum possible score of 100, respondent's median score ranged from 30 to 50 for knowledge related to sexual physiology, STIs/HIV/AIDS and contraception. For these three categories of knowledge, respondents with hearing and physical disabilities or from rural areas scored lower than their counterparts with visual disabilities or from urban areas. The multivariate analyses showed that the residential area and education level were strong correlates of knowledge among respondents with visual and hearing disabilities. Other significant correlates were age for respondents with visual impairment and physical impairment, and single child status in the family and father's education level for respondents with hearing impairment. Sources of and barriers and preferences in accessing SRH information differed by type of disabilities, residential areas and gender. In general, school teachers were the primary and most preferred sources of SRH knowledge, followed by the Internet, peers/friends and parents. Unaware of where to get accurate information and feeling embarrassed to seek information were the two most frequently mentioned barriers in accessing SRH information. Conclusion Respondents had poor knowledge of SRH and limited access to SRH information, especially those from rural areas. Efforts should be made to promote school and family-based sexuality education tailored for youth with different types of disabilities.